2018
DOI: 10.33590/emjinnov/10313113
|View full text |Cite
|
Sign up to set email alerts
|

Automated Item Generation: The Future of Medical Education Assessment

Abstract: A major innovation in psychometric science, termed automated item generation (AIG), holds the potential to revolutionise assessment in medical education. In short, AIG involves leveraging the expertise of content specialists, item templates, and computer algorithms to create a variety of item permutations, often resulting in hundreds or thousands of new items based on a single item model. AIG may significantly improve item writing capabilities, reduce human error, streamline efficiencies, and reduce costs for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…While repeated iterations and parameter tweaking (e.g., by adjusting top_p and temperature to increase or decrease linguistic diversity) can often offer quick relief, some PIG executions may yield less useful items than others. Importantly, no form of automated item generation currently available fully obviates the need for formal quality checks and human review (Goldenfein, 2019; Köbis & Mossink, 2021; Royal et al, 2019). That is, even within the best iterations, most of what the PIG—or any other comparable algorithm—generates will not be usable and the onus is one the researcher to read, assess, and organize the extensive algorithmic output to select suitable items.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While repeated iterations and parameter tweaking (e.g., by adjusting top_p and temperature to increase or decrease linguistic diversity) can often offer quick relief, some PIG executions may yield less useful items than others. Importantly, no form of automated item generation currently available fully obviates the need for formal quality checks and human review (Goldenfein, 2019; Köbis & Mossink, 2021; Royal et al, 2019). That is, even within the best iterations, most of what the PIG—or any other comparable algorithm—generates will not be usable and the onus is one the researcher to read, assess, and organize the extensive algorithmic output to select suitable items.…”
Section: Discussionmentioning
confidence: 99%
“…The aforementioned process also highlights other significant start-up costs that come with AIG: First, in the form described above, AIG is anything but automatic and extensive preparatory steps are required before any automation takes place (Kosh et al, 2019). Second, in order to actually use computer algorithms, one must either be able to train them—which requires expertise and large computational storing and processing capacities (Fetaya et al, 2020)—or gain access to existing software, which has hitherto not been widely available (Royal et al, 2019).…”
Section: Automated Item Generationmentioning
confidence: 99%
“…7 However, there is little work into generating large volumes of clinical vignettes in an automated way. While variations of a technique called Automated Item Generation (AIG) (a template-based, expert-informed process) 4 have been used in the past, we were unable to find examples in the literature of using chatbots or conversational AI for this purpose. This study explores the use of a modern conversational agent (aka chatbot), specifically ChatGPT, for generating and evaluating clinical vignettes.…”
Section: Introductionmentioning
confidence: 95%
“…3 Development of these health education items is also expensive, with a similarly constructed item, multiple choice test questions, estimated at a cost of $1500-2500 each. 4 Previous studies have proposed systematic frameworks for developing vignettes for health professionals, 2 methods for evaluating vignette content validity, 5 and integrating co-design into the vignette creation process. 6 A recent review that aimed to synthesize vignette methodology in qualitative healthcare research suggested that this methods-focused work was necessary, arguing that the variability between development methods demonstrated the need for a more rigorous, transparent vignette development process.…”
Section: Introductionmentioning
confidence: 99%
“…The most popular tool for testing in medical education are exams comprised of multiplechoice questions (MCQs) (Douthit et al, 2021;Grainger et al, 2018). Besides allowing for instant scoring, MCQs are suitable for achievement testing since they cover different skills and enable the assessment of numerous candidates in a cost and resource efficient manner (Royal et al, 2018;Rust et al, 2020).Writing MCQs is complex since experts must outline and replicate cognitive problem-solving skills (Billings et al, 2020;. In order to plan this procedure, experts must share their knowledge and collaborate behind the scenes.…”
Section: The Role Of Multiple-choice Questions In Medical Educationmentioning
confidence: 99%